THE MAIN FEATURES OF CARGO INSURANCE IN ISLAMIC LAW AND ITS FUTURE - Shoymardonova Mushtariybegim Alisher kizi (Western European Studies, 2025)
This article delves into the fundamental aspects of Islamic cargo insurance, known as Takaful, and explores its distinctive features compared to conventional insurance. It outlines the principles underpinning Takaful, including mutual cooperation, risk-sharing, and adherence to Sharia law, which prohibits interest (riba), excessive uncertainty (gharar), and gambling (maysir). The article also examines the operational models of Takaful, such as Mudarabah and Wakalah, and their applications in insuring cargo. Additionally, it provides insights into the regulatory frameworks and challenges faced by Islamic cargo insurance providers. Looking forward, the article discusses the potential growth and integration of Takaful within the global insurance industry, highlighting the increasing demand for Shariacompliant financial products and the opportunities for innovation and expansion.
Keywords: takaful; Islamic insurance; risk-sharing; sharia-compliance